Age, grain size, geochemical, paleontological,mineralogical and leaf-wax biomarker data from lake Voёlvlei, South Africa - Strobel, Paul; Bliedtner, Marcel; Carr, Andrew S; Frenzel, Peter; Klaes, Björn; Salazar, Gary; Struck, Julian; Szidat, Sönke; Zech, Roland; Haberzettl, Torsten (PANGAEA, 2021)
South Africa is a key region to reconstruct and understand past changes in atmospheric circulation, i.e. temperate Westerlies and tropical Easterlies. Here we present a new record from the coastal wetland Voёlvlei (Lat: 34.013° S; Lon: 22.904° E; 5 m above present sea level), which is situated in the year-round rainfall zone of South Africa on the southern Cape coast, published by Strobel et al. (2021; doi:10.5194/cp-17-1567-2021). A 13 m long sediment core was retrieved and analysed using a multi-proxy approach to investigate both sea-level and environmental changes during the past ~8.5 ka. A robust chronology was established using various dating approaches including OSL and 14C of bulk TOC, organic macrofossils, charcoal and n-alkanes. Our data consist of compound-specific carbon and hydrogen stable isotopes of leaf wax n-alkanes as well as sedimentological assays of inorganic and organic elemental compositions, and paleoecological analyses on fossil remains. For additional information and paleoclimatic interpretation please see Strobel et al. (2021; doi:10.5194/cp-17-1567-2021).
Keywords: compound-specific stable isotopes; Geochemistry; Holocene climate; n-alkanes; sea-level change; South Africa